Paradigma Masyarakat Tentang Wakaf Tunai (Cash Waqf) - Muhammad Sholeh Khan (Al-Sharf: Jurnal Ekonomi Islam, 2022)
Cash waqf is one of the important instruments in generating the social economy of the people. The need for encouragement and thoughts from various parties such as the government, religious leaders, and the entire community to support the implementation of the cash waqf. However, due to the lack of educational understanding about cash waqf, many people do not understand. This study aims to determine the paradigm of the community as well as their understanding of cash waqf at Perumnas Batu Anam, Siantar District, Simalungun Regency. This study uses a qualitative approach with data sourced from observations and direct interviews with the surrounding community. This study found that there are many people who do not understand about cash waqf due to the lack of education and socialization as well as supporting literature about cash waqf. The low paradigm and public understanding of cash waqf causes a threat to the existence and implementation of cash waqf among the community. The solution to this problem is to carry out regular socialization in various places as a form of effort in grounding cash waqf for the benefit of the community.